A meso-mechanics-based experimental method for characterizing the in-plane compressive properties of aramid paper. (May 2021) - Yang, Weichao; Zhang, Xufeng; Pan, Bing; Ding, Bin; Fei, Binjun; Yi, Xiaosu; Chen, Yuli
Abstract: Aramid paper honeycomb cores have been extensively used in lightweight structures. However, compressive properties of the paper, which are important for predicting the mechanical behaviors of honeycomb cores, can hardly be accurately measured due to the weak out-of-plane bending stiffness. Here, we propose an experimental method to characterize the in-plane compressive properties of the paper, in which the paper is processed into a laminate by the adhesive between layers to prevent the out-of-plane buckling. We also conducted a meso-mechanics model to analyze the compressive behavior. The compressive modulus of the hybrid paper obtained from our proposed method is basically identical to the tensile modulus, and the strength is much larger than previous estimations due to effectively avoiding the buckling. Then the compressive properties are used in numerical simulations to study the compressive properties of hybrid paper honeycombs, and the simulation calculated compressive modulus and strength agree well with experimental results, which verifies the accuracy of our method. This meso-mechanics-based characterization method can be applied to other types of paper and paper-like materials as well. Highlights: A meso-mechanics-based experimental characterization method for paper is proposed. The method can characterize the in-plane compressive properties of paper accurately. The tested paper properties can give a better prediction of honeycomb properties.